Multiaxial fatigue of in-service aluminium longerons for helicopter rotor-blades (Fracture and Structural Integrity, 2018)
Fatigue cracking of longerons manufactured from Al-alloy AVT-1 for helicopter in-service rotor-blades was considered and crack growth period and equivalent of tensile stress for different blade sections were estimated. Complicated case of in-service blades multiaxial cyclically bending-rotating and tension can be considered based on introduced earlier master curve constructed for aluminum alloys in the simple case of uniaxial tension with stress R-ratio near to zero. Calculated equivalent tensile stress was compared for different blade sections and it was shown that in-service blades experienced not principle difference in this value in the crack growth direction by the investigated sections. It is not above the designed equivalent stress level. Crack growth period estimation in longerons based on fatigue striation spacing or meso-beach-marks measurements has shown that monitoring system introduced designer in longerons can be effectively used for in-time crack detecting independently on the failed section when can appeared because of various type of material faults or in-service damages.
Keywords: Fatigue; Multiaxial; Longerons; Aluminium alloy; Crack growth; Fractography; Stress equivalent